2021
DOI: 10.1186/s12909-021-02793-7
|View full text |Cite
|
Sign up to set email alerts
|

Student-run free clinic volunteers: who they are and what we can learn from them

Abstract: Background Initiatives employing medical students’ volunteerism and idealism, such as the Student-Run Free Clinics (SRFC) program, are prevalent in US medical schools. Many studies evaluated various aspects of volunteering, sometimes resulting in conflicting evidence. This study simultaneously sought to identify the characteristics of volunteers vs. non-volunteers, and to characterize the volunteers’ perception of the SRFC. Methods We administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
2
5
0
Order By: Relevance
“…The results of this study show that there is equal participation in volunteering from a gender perspective, with both female and male students exhibiting a similar level of involvement in volunteering activities, though the percentage of females (76.5%) among the studied population is far more than that of the males (23.5%). Our results concur with other studies suggestion that medical students' gender is not statistically different between volunteers vs. non-volunteers yet, there may be tendencies for volunteers to be female 23 . Additionally, the level of participation in volunteering activities among non-UAE nationals was significantly higher than that of the UAE nationals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study show that there is equal participation in volunteering from a gender perspective, with both female and male students exhibiting a similar level of involvement in volunteering activities, though the percentage of females (76.5%) among the studied population is far more than that of the males (23.5%). Our results concur with other studies suggestion that medical students' gender is not statistically different between volunteers vs. non-volunteers yet, there may be tendencies for volunteers to be female 23 . Additionally, the level of participation in volunteering activities among non-UAE nationals was significantly higher than that of the UAE nationals.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in the average number of volunteering across the three categories of annual GPA and towards the higher annual GPA group was trivial. Yet, our observations support the findings of previous literature, which suggested that students with higher levels of service/service-learning performed better in several important measures of academic success, including class rank (GPA), measure of clinical knowledge, and residency director ratings 23 , 29 . There are many factors which could contribute to this finding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Medical students experienced common shared obstacles, including tension between personal safety and professional duty (38%), and were often concerned about COVID’s impacts on society (44%) [ 34 ]. Prosocial motivation may be a component of student volunteering; student volunteers may be more engaged with their local communities than students who do not volunteer [ 35 ]. The choice to volunteer as a medical provider during a crisis may also be due to an individual’s altruistic tendencies, in addition to the desire to impact local spaces [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…One proposed solution for interprofessional education and collaboration is student-run free clinics. By relying on interested students and faculty, these clinics avoid bias towards interprofessional education [ 23 ] and offer peer-to-peer teaching, which is considered an asset [ 22 ]. Students care for complex patients and better understand the role of teams in patient care [ 24 ].…”
Section: Introductionmentioning
confidence: 99%